Strengthening the CEO–CFO interplay: The role of regulatory focus and similar compensation plans - Firk, Sebastian; Detzen, Nina; Hennig, Jan C.; Wolff, Michael (Accounting, Organizations and Society, 2024)
In this study, we examine how personality attributes and a coordinated compensation design jointly contribute to complementarity in the CEO–CFO dyad. Drawing on regulatory focus theory, we propose that the combination of a CEO with a promotion focus and a CFO with a prevention focus benefits firms. In such a dyad, promotion-focused CEOs bring creativity, speed, and eagerness to advancement, whereas prevention-focused CFOs attend to vigilance, helping to keep promotion-focused CEOs grounded. We further argue that the effectiveness of this CEO–CFO dyad depends on promotion-focused CEOs being open to critical advice from prevention-focused CFOs. To make CEOs more amenable to CFOs' advice, we suggest similar compensation plans that foreground common objectives. We empirically test our arguments by focusing on the CEO–CFO dyad's influence on investment spending and firm performance in a longitudinal sample covering more than 10,000 firm years. Our results indicate a positive association between CEO promotion focus and investment spending, as well as firm performance. We further find that CFO prevention focus weakens the association between CEO promotion focus and investment spending, but strengthens the association with firm performance. These moderating influences of CFO prevention focus are more pronounced for higher compensation similarity in the CEO–CFO dyad. In sum, our findings exemplify that deliberately considering CEO and CFO personality attributes and their compensation design jointly strengthens the functioning of the CEO–CFO dyad.